Moderate mitral regurgitation in association with ventricular septal defect in children: Does it warrant mitral valve repair? - Hao Siang Ong; Sivakumar Krishnasamy; Retnagowri Rajandram; Asthika Amirthalingam; Tengku Nazim Tengku Yusof; Sivakumar Sivalingam (Annals of Pediatric Cardiology)
Background: The management of ventricular septal defect (VSD) alongside mitral regurgitation (MR) in pediatric patients remains a contentious issue due to the intricacies of cardiac surgery and the need to minimize ischemic time. Despite observations of MR regression following VSD closure, definitive guidelines for this patient subset are lacking, particularly concerning the management of the subgroup of patients with moderate MR. The objective of the study is to explore the factors influencing the choice between surgical intervention and conservative management for the mitral valve (MV) in VSD patients with moderate MR. Materials and Methods: A retrospective cohort study from January 2000 to December 2015, we analyzed management trends and focused on 53 patients with both VSD and moderate MR. This cohort was subdivided into four groups: first by their MV pathology, and then stratified by the receipt of intervention towards the diseased MV. Our primary goal was to identify correlations, especially concerning surgical outcomes such as mortality and need for re-operation. Statistical significance is determined when the P value is lower than 0.05. Results: There were no notable differences in preoperative variables across four cohort groups, apart from the cross-clamp duration which was longest in Group B intervention. Outcome analysis showed survival rates that were higher in cohort groups that underwent intervention toward the disease MV regardless of existing MV morphology, although results were not statistically significant. Cox model analysis found no correlation between the cohort groups and postoperative outcomes, but cross-clamp duration significantly correlated with mortality. Conclusions: In cases of VSD with moderate MR with associated pathologies of the valvular apparatus, opting for MV repair (MVr) appears to improve survival outcomes without significantly increasing postoperative morbidity. Similarly, for patients with moderate MR and isolated annular dilatation, surgical MVr is observed to have better survival trend compared to the control group.